2019
DOI: 10.1111/hsc.12877
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregivers’ experiences of caring for persons with dementia in Estonia: A narrative study

Abstract: This paper presents the results of a qualitative study aimed at exploring the experiences and needs of informal caregivers of persons with dementia and identifying caregiver expectations for support. The research was based on phenomenological and social constructionist approaches; it also took experience-centred and culturally oriented approaches to narratives. It was conducted in Estonia in 2017 by means of unstructured in-depth interviews with 16 informal caregivers who had relatives with dementia. The narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Hence, previous findings which found that primary carers tend to have higher subjective burden are supported (Gonçalves-Pereira et al, 2020). In accordance with the findings by Varik et al (2019), the personal life of carers experiencing a crisis is (type 'There is no alternative, you have to live with it') or was for some time (types 'Acting strategic is making it work' and 'Reflect the situation, deal with it, and pull it through') almost completely determined by the demands related to the care situation. Restrictions in privacy and in the fulfilment of personal needs are important factors of carer burden (Ransmayr et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, previous findings which found that primary carers tend to have higher subjective burden are supported (Gonçalves-Pereira et al, 2020). In accordance with the findings by Varik et al (2019), the personal life of carers experiencing a crisis is (type 'There is no alternative, you have to live with it') or was for some time (types 'Acting strategic is making it work' and 'Reflect the situation, deal with it, and pull it through') almost completely determined by the demands related to the care situation. Restrictions in privacy and in the fulfilment of personal needs are important factors of carer burden (Ransmayr et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies indicated that the perception of care as burdensome is related to the perceived need to constantly oversee the person with dementia and to continuously coordinate his/her life, as well as to the lack of or dissatisfaction with social support (Benson et al, 2019;Brügger et al, 2016;Garcia-Mochon et al, 2019;Lopez Hartmann et al, 2019). This degree of commitment is time-consuming and results in restrictions in personal life, such as limited time to pursue one's own interests, loss of freedom and feelings of loneliness or social isolation (Brügger et al, 2016;Large & Slinger, 2015;Ransmayr et al, 2018;Varik et al, 2019). Thus, finding a balance between meeting care demands and pursuing personal goals appears to be challenging for carers (Lopez Hartmann et al, 2016;Quinn et al, 2015;Rayment et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver overload manifests itself as a state of emotional exhaustion, stress and fatigue (Cabote, Bramble, & McCann, 2015; Gräske et al., 2018) and, furthermore, as many other consequences reflected in caregivers feeling dissatisfied with their overall health (Millenaar et al., 2016). Social dysfunction, anxiety and insomnia are prevalent symptoms in family caregivers of patients with dementia of the Alzheimer's type (Ruiz Fernández & Ortega Galán, 2019; Varik, Medar, & Saks, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This contribution is substantial for the health care system [7]. While the contribution is important, informal caregivers are often exposed to emotional strain, relationship deprivation, family conflicts and financial burden, which can impact their health and life quality [8]. Compared to other informal caregivers, those who care for older people with cognitive decline experience an even greater burden.…”
Section: Introductionmentioning
confidence: 99%
“…Even a newly acquired role as a caregiver affects other roles and often results in additional burden and emotional strain. This case will become worse especially when a caregiver has no prior experience in caregiving [8]. Moreover, family members often need to transition their relationship with the parent or spouse from that of a family member to that of a proactive caregiver.…”
Section: Introductionmentioning
confidence: 99%